22: Argumentation in AI and law - Sartor, Giovanni (Edward Elgar Publishing, 2026)
This chapter investigates formal models of argumentation developed by scholars working at the nexus of AI and the law. It argues that these models successfully capture important aspects of legal reasoning. First, the chapter presents models that move beyond deduction, address defeasibility, and engage with argumentation. Second, it introduces a formal account of legal argumentation in which the notion of an argument is defined, dialectical conflicts between arguments are analysed, priorities are considered, and a method for assessing the status of arguments and their conclusions is proposed. The method allows us to determine whether an argument is to be classified as justified, defensible, or to be rejected, relative to the conflicting arguments that are constructible from a given set of legal premises. The possibility of applying this model to different aspects of legal reasoning is discussed.